(untitled) (American Journal of Islam and Society, 2007)
The book’s title and subtitle are both concise and apt characterizations. After more than sixty years of work as a translator and a writer, Johnson-Davies takes the reader on a journey through memories told as if relived through writing. The language is clear, fluent, and businesslike. Interspersed in the account are humorous anecdotes about some of his more embarrassing experiences as a translator. The book has a foreword by Naguib Mahfouz (d. 2006), the Nobel Prizewinning (1988) Egyptian writer with whom the author had an acquaintanceship going back sixty years and several of whose books he translated. Twenty-two photographs show the author at various times in his life (1922- 2000) at work, with friends, writers, poets, and various personalities. Every photograph is fully documented as regards location, names, date, and other ...